EFFECT OF VARIATIONS IN HYDROLYSIS TIME ON CARBOHYDRATE LEVELS OF WHITE RICE FLOUR (Oryza sativa L.) USE OF THE SCHOORL LUFF METHOD - Zulfisa, Zulfisa; Renatalia Fika; Ainun Naim; Ezy Wirna (Lembaga Pengembangan Kinerja Dosen, 2022)
For humans, carbohydrates are a crucial nutrient that the body uses to produce energy. Additionally, carbohydrates aid in the body's digestion of extra protein. White rice flour (Oryza sativa L.) is a common energy source in the community with a high carbohydrate content. This research was done to find out how different hydrolysis times affected the amount of carbohydrates in white rice flour (Oryza sativa L.). The Schoorl Luff method is used to determine the carbohydrate content of commercial white rice flour. HCl 1 N was used as a catalyst to hydrolyze white rice flour, with different hydrolysis periods of 60 minutes, 90 minutes, 120 minutes, 150 minutes, and 180 minutes. A schoorl luff, a source of Cu2+, was used to assess the hydrolysis results and titrated iodometrically. With a time of 180 minutes and a weight-to-water ratio of 63.99%, the findings of determining the ideal carbohydrate content in commercial white rice flour were obtained.